(untitled) (Experimental biology, 2016)
Antagonistic activity of 50 isolates of extremophilic actinomycetes was examined in vitro in different habitats - neutral (medium 1, pH 7.0), saline (medium 2 with 2.5% NaCl, pH 7.0), alkaline (medium 3 with 0.25 % Na2CO3, pH 8.0) conditions using 11 species of phytopathogenic fungi. 9 isolates exhibited high specific activity against alternariosis agents, 7 isolates - against aspergillosis agents, 13 isolates - against piriculariosis agents. Isolate K-541 showed the highest activity against all the strains of the examined test organisms belonging to genera Fusarium, Alternaria, Pyricularia, Bipolaris, Aspergillus (inhibition zone diameter is of 20-56 mm). Antibiotic activity of the isolate K-541 against fungi of the Fusarium genus is 30-45 mm in neutral conditions, 40-48 mm in salty conditions, 20-33 mm in alkaline conditions.